Nucleotide sequences of the microsatellite locus Du215 (arm) allelic variants in the parthenospecies Darevskia armeniaca (Lacertidae) - Malysheva, D. N.; Vergun, A. A.; Tokarskaya, O. N.; Sevast’yanova, G. A.; Darevsky, I. S.; Ryskov, A. P. (Russian journal of genetics, 2007)
Using monolocus PCR analysis with the pairs of primers designed for the Du215 locus of Darevskia unisexualis, allelic polymorphism at the orthologous locus in the populations of the related parthenospecies D. armeniaca was investigated. It was demonstrated that Du215 (arm) locus was polymorphic and in the populations of parthenospecies D. armeniaca (n = 127) represented by at least three allelic variants, differing from each other by the size and composition of microsatellite cluster, and by single nucleotide substitutions in flanking DNA. Unlike the Du215 locus, Du215 (arm) was shown contain not only GATA, but also (GACA) repeats, which were absent in D. unisexualis. Thus, in this study, the data on the molecular nature of allelic polymorphism at one of the microsatellite loci of the parthenospecies D. armeniaca were reported.